Comparative genomics of 43 strains of Xanthomonas citri pv. citri reveals the evolutionary events giving rise to pathotypes with different host ranges. (December 2015) - Gordon, Jonathan; Lefeuvre, Pierre; Escalon, Aline; Barbe, Valérie; Cruveiller, Stéphane; Gagnevin, Lionel; Pruvost, Olivier
Abstract Background The identification of factors involved in the host range definition and evolution is a pivotal challenge in the goal to predict and prevent the emergence of plant bacterial disease. To trace the evolution and find molecular differences between three pathotypes ofXanthomonas citri pv.citri that may explain their distinctive host ranges, 42 strains ofX. citri pv.citri and one outgroup strain, Xanthomonas citri pv.bilvae were sequenced and compared. Results The strains from each pathotype form monophyletic clades, with a short branch shared by the Aw and A pathotypes. Pathotype-specific recombination was detected in seven regions of the alignment. Using Ancestral Character Estimation, 426 SNPs were mapped to the four branches at the base of the A, A*, Aw and A/Aw clades. Several genes containing pathotype-specific nonsynonymous mutations have functions related to pathogenicity. The A pathotype is enriched for SNP-containing genes involved in defense mechanisms, while A* is significantly depleted for genes that are involved in transcription. The pathotypes differ by four gene islands that largely coincide with regions of recombination and include genes with a role in virulence. Both A* and Aw are missing genes involved in defense mechanisms. In contrast to a recent study, we find that there are an extremely small number of pathotype-specific gene presences and absences. Conclusions The three pathotypes ofX. citri pv.citri that differ in their host ranges largely show genomic differences related to recombination, horizontal gene transfer and single nucleotide polymorphism. We detail the phylogenetic relationship of the pathotypes and provide a set of candidate genes involved in pathotype-specific evolutionary events that could explain to the differences in host range and pathogenicity between them.